Are two views better than one? Investigating three-quarter view facial composites. Issue 4 (9th November 2015) - Ness, Hayley; Hancock, Peter J.B.; Bowie, Leslie; Bruce, Vicki; Pike, Graham
Abstract : Purpose: – The introduction of a three-quarter-view database in the PRO-fit facial-composite system has enabled an investigation into the effects of image view in face construction. The purpose of this paper is to examine the impact of constructing full-face and three-quarter-view composites under different encoding conditions. It also examines the potential value of three-quarter-view composites that can be generated automatically from a front-view composite. The authors also investigate whether there is an identification benefit for presenting full-face and three-quarter composites together. Design/methodology/approach: – Three experiments examine the impact of encoding conditions on composite construction and presentation of composites at the evaluation stage. Findings: – The work revealed that while standard full-face composites perform well when all views of the face have been encoded, care should be taken when a person has only seen one view. When a witness has seen a side view of a suspect, a three-quarter-view composite should be constructed. Also, it would be beneficial for a witness to construct two composites of a suspect, one in full-face view and one in a three-quarter-view, particularly when the witness has only encoded one view. No benefit emerged for use of three-quarter-view composites generated automatically. Research limitations/implications: – This is the first study to examine viewpoint in facial composite construction. While a great deal of research has examined viewpoint dependency in face recognition tasks, composite construction is a reconstruction task involving both recall and recognition. The results indicate that there is a viewpoint effect that is similar to that described in the recognition literature. However, more research is needed in this area. Practical implications: – The practical implications of this research are that it is extremely important for facial composite operators in the field (police operators) to know who will make a good likeness of the target. Research such as this which examines real-life issues is incredibly important. This research shows that if a witness has seen all views of a perpetrator's face then standard composite construction using a full-face view will work well. However, if they have only seen a single view then it will not. Social implications: – There are obvious wider societal implications for any research which deals with eyewitness memory and the potential identification of perpetrators. Originality/value: – No research to date has formally examined the impact of viewpoint in facial-composite construction.